IV International scientific and practical conference "Reserves of the Crimea. Biodiversity and nature conservation in the Azov-Black Sea region" (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
IV International scientific and practical conference "Reserves of the Crimea. Biodiversity and nature conservation in the Azov-Black Sea region"